2016
DOI: 10.1021/acs.energyfuels.5b02600
|View full text |Cite
|
Sign up to set email alerts
|

Coke Formation and Coupled Effects on Pore Structure and Permeability Change during Crude Oil in Situ Combustion

Abstract: In situ combustion (ISC) is an important thermal recovery technique. Significant open ISC questions include the effect of coke formation on the pore structure and permeability. In the study, an experimental apparatus was constructed to not only physically simulate coke formation similar to the crude oil ISC process but also to in situ measure postdeposition permeability. Effects on coke deposition with the Xinjiang crude oil were studied, including reaction atmosphere, temperature, and time. The results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 26 publications
0
40
0
Order By: Relevance
“…In this stage, the side-chain aliphatic hydrocarbon carbon of petroleum coke burns and gives off heat. According to the solid 13 C NMR spectrum of coke, 14 the content of saturated aliphatic hydrocarbon carbon in the petroleum coke formed at 500 °C in the case of sp 3 hybridization decreases significantly with the increase in coking temperature. When the final temperature rises to 678 °C, the pyrolysis process becomes strongly exothermic, which is the third stage of the exothermic reaction process.…”
Section: Resultsmentioning
confidence: 99%
“…In this stage, the side-chain aliphatic hydrocarbon carbon of petroleum coke burns and gives off heat. According to the solid 13 C NMR spectrum of coke, 14 the content of saturated aliphatic hydrocarbon carbon in the petroleum coke formed at 500 °C in the case of sp 3 hybridization decreases significantly with the increase in coking temperature. When the final temperature rises to 678 °C, the pyrolysis process becomes strongly exothermic, which is the third stage of the exothermic reaction process.…”
Section: Resultsmentioning
confidence: 99%
“…Alade et al (2019) investigated the changes in oil composition under combustion and a pyrolysis process (nitrogen gas injection) and concluded that combustion resulted in a higher conversion rate . Xu et al (2016) reported the impacts of in situ combustion on pore configurations and permeability . It was found that the coke deposition in pores turned large pores into micropores which deteriorated permeability.…”
Section: Css Follow-up Processes and Simulationmentioning
confidence: 99%
“…Normal fire flooding production can also be achieved, but the effective time of the surrounding production wells is delayed by 4-6 months [7,16]. This shows that the viscosity of heavy oil has a certain impact on the combustion dynamics and the injectionproduction parameters of fire flooding, which leads to high risk and difficulty to grasp the economy of high-viscosity heavy oil fire flooding [17]. The goals of this study were to conduct one-dimensional combustion tube tests using heavy oil with different viscosities and to clarify the influence of the viscosity on the temperature, gas composition, air injection pressure, and production parameters of fire flooding in order to provide a basis for the formulation of a highviscosity oil reservoir fire flooding plan and the construction of supporting oilfield facilities.…”
Section: Introductionmentioning
confidence: 99%